AN ANALYSIS OF SLANG WORD IN SONG LYRICS EMINEM ON ALBUM KAMIKAZE - Fernando Charlino Haspo; Rusdi Noor Rosa (Universitas Negeri Padang, 2018)
This research paper is entitled “An Analysis of Slang Word in Song Lyrics Eminem on Album Kamikaze.” This study was intended to find out the slang words that appear in the lyrics of the song of Eminem and classification of slang words in song lyrics of Eminem on album Kamikaze. The method of the research was qualitative descriptive method. The research got the data from transcript, which was from the internet. The writer uses transcript of this song as his main sources, the sources of data are 5 transcripts of the lyrics of the song by Eminem. Data obtained from the data collection through reading and comprehending the lyrics, the data were analyzed based on the theories of word formation proposed by Yule (2006). Based on the data analysis, it was found that there are 4 out of 9 types of word. They are (1) Coinage, (2) Compounding, (3) Blending, (4) Clipping, (5) Converstion, (6) Acronym, (7) Derivation, (8) Back-formation, and (9) Multiple Processes. Among the 4 types of word formation found, the type of word formation most frequently used in Eminem song lyrics on album Kamikaze is clipping with the frequency of 50 data (84%). This finding shows that Eminem in song lyrics mostly used clipping to make the rhyme and beat balance.